Metode TOPSIS Dalam Sistem Pakar Pendiagnosa Penyakit Pada Tanaman Durian - Juhartini, Juhartini; Ramdan, Hendri; Karim, Muh. Nasirudin (STMIK Banjarbaru, 2025)
Durian plants are susceptible to pests and diseases which have an impact on reducing productivity and fruit quality. To overcome this obstacle, a web-based expert system was developed using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method, which can help farmers diagnose diseases in durian plants quickly and precisely. This expert system was developed using the PHP and MySQL programming languages, and uses a number of symptom variables as input. This research produces an expert system application that can help identify pests and diseases in Durian plants, so that it can be an effective solution in dealing with diagnostic problems correctly. Through a series of validation tests on 10 real test cases, the system showed an accuracy rate of 90% according to expert preferences in diagnosing diseases in Durian plants.Keywords: Diseases in Durian Plants; Expert system; Topsis Method; Web Based AbstrakTanaman Durian rentan terserang hama dan penyakit yang berdampak pada penurunan produktivitas dan kualitas buah. Untuk mengatasi kendala ini, dikembangkan sistem pakar berbasis web menggunakan metode TOPSIS (Technique for Order Preference by Similarity to Ideal Solution), yang dapat membantu petani dalam mendiagnosis penyakit pada tanaman durian secara cepat dan tepat. Sistem pakar ini dikembangkan dengan menggunakan bahasa pemrograman PHP dan MySQL, dan menggunakan sejumlah variabel gejala sebagai input. Penelitian ini menghasilkan sebuah aplikasi sistem pakar yang dapat membantu dalam mengidentifikasi hama dan penyakit pada tanaman Durian, sehingga dapat menjadi solusi efektif dalam menangani permasalahan diagnosis secara tepat. Melalui serangkaian uji validasi terhadap 10 kasus uji nyata, sistem menunjukkan tingkat akurasi 90% sesuai dengan preferensi pakar dalam mendiagnosis penyakit pada tanaman Durian.